2007
DOI: 10.1016/j.bbabio.2007.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Both chlorophylls a and d are essential for the photochemistry in photosystem II of the cyanobacteria, Acaryochloris marina

Abstract: We have measured the flash-induced absorbance difference spectrum attributed to the formation of the secondary radical pair, P(+)Q(-), between 270 nm and 1000 nm at 77 K in photosystem II of the chlorophyll d containing cyanobacterium, Acaryochloris marina. Despite the high level of chlorophyll d present, the flash-induced absorption difference spectrum of an approximately 2 ms decay component shows a number of features which are typical of the difference spectrum seen in oxygenic photosynthetic organisms cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 39 publications
6
64
0
Order By: Relevance
“…In addition, some other studies using partially purified samples support our view (28,29). However, for another study using partially purified samples, a different component (Chl a and Chl d heterodimer) was proposed for the special pair (30). Additionally, in an earlier study, Shevela et al (31) proposed that the redox potentials of the wateroxidizing complex in its different S i states (donor side of PS II) are almost the same for A. marina cells and spinach thylakoids.…”
Section: Discussionmentioning
confidence: 48%
“…In addition, some other studies using partially purified samples support our view (28,29). However, for another study using partially purified samples, a different component (Chl a and Chl d heterodimer) was proposed for the special pair (30). Additionally, in an earlier study, Shevela et al (31) proposed that the redox potentials of the wateroxidizing complex in its different S i states (donor side of PS II) are almost the same for A. marina cells and spinach thylakoids.…”
Section: Discussionmentioning
confidence: 48%
“…Calculations of the TÀS spectra of D1D2cytb559 complexes and comparison with experimental data revealed that the triplet is localized on Chl D1 . [32] Direct evidence was provided by Schlodder et al [60] from TÀS spectra on mutants ( Figure 5) of PS-II core complexes from Synechocystis sp. PCC 6803.…”
Section: The State 3 Chl Where the Triplet Energy Localizesmentioning
confidence: 81%
“…This time con- Figure 12. The experimental P + Q A À ÀPQ A difference spectrum [60] at 77 K is compared with calculations [70] assuming a Chla homodimer or a Chla-Chld heterodimer in the "special pair" of A. marina. Comparison between experimental fluorescence decay of PS-II core complexes at 300 K, measured after excitation with a 100 fs optical pulse that was centered at 663 nm (*), [74] in comparison to the "exact" calculations (c) and calculations that assume fast exciton equilibration in compartments consisting of CP43-Chlz D1 , CP47-Chlz D2 , and the six core pigments of the RC (a) or fast exciton equilibration in the whole PS-II core complex (g).…”
Section: Relative Timescales Of Excitation Energy Transfer and Trappingmentioning
confidence: 99%
“…However, in the case of A. marina, the redshifted oxidation spectrum of P 740 (8,38,39) strongly overlaps with the oxidation spectrum of plastocyanin (the redox changes of which are commonly followed in the 810 -870 nm region), making the direct observation of plastocyanin redox changes using optical spectroscopy difficult.…”
Section: Methodsmentioning
confidence: 99%